PEKANBARU CITY ELECTION COMMISSION'S CAPABILITY IN MANAGING ADHOC ELECTION ORGANIZING BODIES IN THE 2019 SIMULTANEOUS ELECTIONS: - Muchid Albintani; Tri Joko Waluyo; VEGA (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The 2019 simultaneous elections are known as complicated and difficult elections, especially for election organizers at the Adhoc Election Organizing Body (BPP) level. So that many victims fell from the BPP Adhoc election. The capability of the Pekanbaru City KPU in managing the ad hoc BPP is the main problem in the implementation of the 2019 simultaneous elections. This study aims to find out how the Pekanbaru City General Election Commission (KPU) is capable of managing Ad Hoc Election Organizing Bodies (BPP) in the 2019 Simultaneous General Elections. used in this study is the core capability of public organizations according to Leonard-Barton, which has 4 variables, consisting of Knowledge and skills, Technical Systems, Managerial Systems, and Values and Norms. This research use desciptive qualitative approach. Data collection techniques were carried out by interviews and documentation. The results of this study are that the General Election Commission (KPU) is not yet capable of managing the Ad Hoc Election Organizing Body (BPP) in the 2019 Simultaneous General Elections. rumi, the Ad Hoc BPP Managerial System is not yet capable, then the Values and Norms carried out by the KPU in the Ad Hoc BPP Management have been achieved, although there are still deficiencies on various sides, especially in the implementation of voting at TPS.